Peeling tape produces strong electric fields via stick–slip friction that drive chemical reactions - Xufeng Gao; Peng Zhou; Xu Yuan; Xiaoxu Li; Bowen Li; Yu Xia; Yifan Meng; Richard N. Zare; Tingting Zheng; Xinxing Zhang (Proceedings of the National Academy of Sciences, 2025)
Adhesive interfaces store significant energy due to interlocking molecular chain entanglement and van der Waals forces. When two adhesive surfaces are separated, triboelectric effects induce charge transfer, generating a strong electric field at the peeling interface. This effect offers different opportunities for initiating chemical reactions. Here, we report that the stick–slip friction involved in peeling tape produces electric fields on the order of 10 9 V/m, as measured by the vibrational Stark shift observed by confocal Raman spectroscopy during tape peeling. This field is sufficiently strong to ionize water and produce the H 4 O 2 + cation, a hydroxyl radical adduct with a hydronium ion. We further demonstrate that this electric field can drive a variety of electron transfer reactions. Our findings suggest that tribocharging presents a promising, energy-efficient avenue for electric-field-driven green chemistry.